Early structure at Fort Nisqually, Washington, approximately 1870 - University of Washington Libraries. Special Collections Division. (1870)
On verso of image: First building, Fort Nisqually. This picture shows the first building at the present location of Fort Nisqually. It was a residence erected by the Hudson Bay Company in 1843. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number Scanned from a photographic print using a Microtek Scanmaker 9600XL at 100 dpi in JPEG format at compression rate 3 and resized to 768x512 ppi. 1999.